Perancangan Identitas Visual Berbasis Religi Dan Budaya Pesisir Di Kota Demak - Agus Rochani (Jurnal Planologi, 2021)
ABSTRACKThe identity of the city is a form of visual that represents the mental image of the average people. Demak as a city on the north coast of Java Island has much historical value in terms of the spread of Islam. The collaboration between the two aspects is very interesting to expres in the form of a visual identity of the city. This study aims to develop a visual identity design based on the religious values and coastal culture in Demak. The research is formulating qualitatively, which is built from natural basic elements, which depart from data, utilizing existing theories as explanatory material and ending with an identity concept. The design of identity adopts Islamic architectural forms and values at the Great Mosque of Demak, which is collaborated with city characters coast, represented by the shape of sea waves, Islamic ornaments and traditional Javanese Demak Djung boats. Key word: regional image, visual identity, mass composition.  ABSTRAKIdentitas visual kota merupakan wujud visual yang mewakili gambaran mental rata-rata masyarakatnya. Kota Demak sebagai kota yang berada ada di pesisir utara Pulau Jawa memiliki nilai historis yang kuat dalam hal penyebaran Agama Islam. Kolaborasi kedua aspek tersebut sangat menarik dituangkan dalam bentuk indentitas visual kota. Penelitian ini bertujuan menyusun rancangan indentitas visual yang dikembangkan berdasarkan nilai nilai religi dan budaya pesisir di Kota Demak. Penelitian dirumuskan secara kualitatif, yang dibangun dari elemen elemen dasar alamiah, yang berangkat dari data, memanfaatkan teori yang ada sebagai bahan penjelas dan berakhir dengan sebuah konsep identitas. Perancangan identitas mengadopsi bentuk dan nilai arsitektural Islam di Masjid Agung Demak, yang dikolaborasi dengan karakter kota pesisir diwakili oleh bentuk ombak air laut, ornamen Islam dan kapal tradisional Demak Djung Jawa.Kata kunci: citra kawasan, identitas visual, gubahan masa.